Impact of Learning Organization Characteristics on Organizational Change in Colleges of Intermediate Studies in Gaza Strip - Abu Deeb, Ahmed Salah (Journal of Economic, Administrative and Legal Sciences, 2022)
This study aimed to identifying the impact of learning organization characteristics on organizational change in colleges of intermediate examinations in the Gaza Strip. The study population was represented by all staff members at the colleges of intermediate studies in the Gaza Strip totaling (1344) employees. The researcher used the descriptive analytical method and the questionnaire as a tool for the study, which were distributed to a random sample of (295) individuals; The study concluded that the perceived level of the staff members of the colleges of intermediate studies in the Gaza Strip regarding the characteristics of learning organization was high., the perception level of the staff members of the colleges of intermediate studies in the Gaza Strip regarding the organizational change was also high, In this respect, results revealed that there was a direct, statistically significant and correlative relation between all learning organization characteristics: (continuing education, encouragement of dialogue, personal empowerment, joint vision, cooperation and collective learning) and the organizational change in the colleges of intermediate studies in the Gaza Strip. Meaning that, the greater is the learning organization characteristics, the greater the organizational change. Results also indicated that there was an impact of the following learning organization characteristics: (cooperation and collective learning, encouragement of dialogue, joint vision, continuing education) respectively on the organizational change. Those characteristics explained (72%) of the total variance in the organizational change.